Sustainable Health Development Becoming Agenda for Public Health Academia - Amirhossein TAKIAN; Ali AKBARI-SARI (Tehran University of Medical Sciences, 2016)
Background: Sustainable Development Goals (SDGs) aim to transform our world, and each goal has specific targets to be achieved by 2030. For the goals to be achieved, everyone needs to do their part: governments, academia, the private sector and all people. This paper summarizes the main evidence-based recommendations made by excellent academics and scholars who discussed their experiences and views during the conference to respond to the challenges of sustainable health development. Methods: To contribute to exploring to the academia's role in reaching SDGs, the 1st International Conference on Sustainable Health Development was held at Tehran University of Medical Sciences, on 24-25 April 2016, in Tehran, Iran. Results: In line with Goal 3 of SDGs: "ensure healthy lives and promote well-being for all at all ages", the conference discussed various aspects of Universal Health Coverage (UHC), as well as Global Action Plans for prevention and control of Non-Communicable Diseases (NCDs), and explained the special role of academic public health institutes in education, research and service provision in the two above-mentioned areas. Conclusion: To fulfill the requirements of SDGs, modern approaches to funding, education, teaching, research priority setting and advocacy, which in turn need novel strategies in collaboration and constructive partnerships among academic public health institutes from low, middle and high-income countries, are essential.